The psychology of esports: trends, challenges, and future directions - Pedraza-Ramirez, I.; Sharpe, B.; Behnke, M.; Toth, A. J.; Poulus, D. R. (Psychology of Sport and Exercise, 2025)
This rapid review examines how sport and exercise psychology (SEP) research has engaged with esports over the last five years, highlighting the academic acceptance of esports in SEP journals and on the psychological factors that influence esports performance and well-being. In addition to searching for recent empirical studies, we identified systematic reviews, meta-analyses, and scoping reviews to capture the breadth of existing syntheses. Following rapid review guidelines (Sabiston et al., 2022) and adapting the PRISMA framework (Page et al., 2021), two systematic searches were conducted in the Web of Science Core Collection and EBSCO host (SPORTDiscus) databases. First, we identified 13 syntheses of the esports literature highlighting the main topics of interest across scholars in relation to SEP. Then, we identified 125 relevant peer-reviewed empirical publications on esports in SEP context, of which 18 appeared in SEP-specific journals. Findings reveal increasing academic attention in affective, cognitive-motor processes, team dynamics, training structures, and health behaviors (e.g., mental health, physical activity, sleep, nutrition) unique to esports while revealing the need for theoretical and methodological attention. Overall, we highlighted how esports and SEP appear to benefit one another in a reciprocal way. Esports offer a controlled, data-rich performance environment for testing and refining SEP theories. Meanwhile, SEP principles enhance professionalism in esports by informing evidence-based training methods and well-being initiatives. Future research should consider longitudinal designs, open science practices, and interdisciplinary collaboration such as data science, sleep medicine, and nutrition to address the nuanced psychological demands in this rapidly evolving performance domain.